A mixed methods process evaluation of a collaborative outpatient palliative care clinic for patients with end-stage liver disease - Warmels, Grace; Wills, Aria; Bruni, Adrianna; Cohen, Leila; Kelly, Erin; Downar, James; Patel, Arpan A.; Dargavel, Greg; Rauthu, Shreya; Isenberg, Sarina R. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Patients with end-stage liver disease (ESLD) have significant symptoms and limited prognosis, yet receive less palliative care (PC) than patients with cancer. The optimal outpatient PC model for patients with ESLD remains unclear. Objective We used process evaluation methodology to evaluate a novel PC clinic for patients with ESLD in Ottawa, Canada. Design We conducted a convergent parallel mixed methods study, informed by a logic model and process evaluation framework co-designed with a caregiver partner. Qualitative inputs included semi-structured interviews conducted with patients, family caregivers, as well as PC and hepatology clinicians, and analyzed using applied thematic analysis. Quantitative inputs included data collected through a retrospective chart review, analyzing healthcare utilization up to six months before and after consultation. Participants Interviews conducted with eight healthcare providers (HCPs) and 13 patients and caregivers. Chart review performed for 46 patients seen in the clinic between October 2020 and June 2023. Intervention An outpatient PC hepatology collaboration clinic, led by specialist PC physicians. Approach Qualitative and quantitative data were analyzed independently and then triangulated for overall interpretation. Key results The evaluation demonstrated the achievement of the outcomes in the logic model and process evaluation domains. Interviews highlighted high satisfaction among HCPs, patients, and caregivers, and effective collaboration between the PC and hepatology teams. Perceived barriers include the burden of in-person appointments. Quantitative results indicated decreased acute healthcare utilization in the six months following PC consultation compared to the six months prior. Over 50% of the deceased patients died outside of the hospital. Conclusion The early outpatient PC clinic provides high-quality, collaborative care for patients with ESLD; study findings suggest an association with reduced acute healthcare utilization and increased likelihood of death occurring outside the hospital. This model represents a promising approach for PC in ESLD and other non-malignant illnesses.